Insights Into Three Frames of Creative Minds: Igniting Perspective Transformation Among First-Year University Students. (April 2020) - Lee, Jae Hwa; Portillo, Margaret; Meneely, Jason
The lens of transformative learning provided a deeper understanding of students' experiences and the process of learning within an interdisciplinary creativity course for first-year college students. Through the thematic analysis of 930 reflective narratives written by 93 students, the research identified how the overall course activities expanded and reframed their insights on creativity. Three frames of creative minds are presented to show the potential for transformations using students' voices about impactful experiences: creative dynamics, transformation as a heightened awareness of the value of creativity to society and self; creative mindsets, transformation as a deeper understanding of diverse aspects of creativity; and creative confidence, transformation as a transfer in perspectives to real-world applications. In addition, the findings from this study proposed a framework to build creative confidence via educational strategies for creative learning.